ChemInform Abstract: Laccase/2, 2, 6, 6‐Tetramethylpiperidinoxyl Radical (TEMPO): An Efficient Catalytic System for Selective Oxidations of Primary Hydroxy and Amino Groups in Aqueous and Biphasic Media. Issue 52 (29th December 2014) - Diaz‐Rodriguez, Alba; Martinez‐Montero, Lia; Lavandera, Ivan; Gotor, Vicente; Gotor‐Fernandez, Vicente
Abstract The reaction can be scaled up.